Severe chronic atopic dermatitis improvement after hepatitis C virus elimination with sofosbuvir/ledipasvir treatment - Szymanek-Pasternak, Anna; Janocha-Litwin, Justyna; Simon, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Chronic hepatitis C virus (HCV) infection is known to be associated not only with chronic hepatitis (CHC) but also with a wide range of extrahepatic manifestations (EHMs). EHMs can be divided into those of a high degree of association with HCV and those with probable or possible association. The first group includes mixed cryoglobulinemic syndrome and B-cell non-Hodgkin’s lymphoma. EHMs that are probably associated with HCV include diabetes mellitus type 2 (T2DM), membrane proliferative glomerulonephritis, neurological impairment, health related quality of life (HRQoL), sicca syndrome, porphyria cutanea tarda and lichen planus while presence of autoantibodies, cardiovascular events and Mooren’s corneal ulcer are possibly associated with HCV infection [1]. Some of these manifestations resolve or significantly improve after HCV elimination which was shown by multiple studies [1, 2].